PERDAGANGAN ORANG DALAM RANAH CYBER CRIME: TANTANGAN DAN PROSPEK PENEGAKAN HUKUM DI ERA DIGITAL - Sari, Neti Mustika; Samawati, Putu (Faculty of Law, University of Palembang, 2024)
Human trafficking has become one of the most disturbing transnational crimes of the 21st century. Meanwhile, advances in information and communication technology have had a significant impact on the dynamics of this crime, with cyber space becoming a new place for perpetrators to carry out human trafficking activities. In this context, this research aims to dig deeper into the criminal act of human trafficking in the realm of cyber crime, highlighting the challenges faced by law enforcement and the prospects for combating it in the digital era. Research findings show that human trafficking in the realm of cyber crime has unique and complex characteristics, including the use of social media, websites and dark web platforms as the main tools for recruiting, promoting and selling victims. Challenges faced by law enforcement include difficulties in collecting legitimate digital evidence, complex cross-border collaboration, and limitations in technical capacity. Increasing international cooperation through more effective information exchange mechanisms, strengthening technical and legal capacity for law enforcement, as well as public awareness about the risks of human trafficking in cyberspace. With these steps, it is hoped that a safer and more sustainable cyber environment will be created, where human trafficking can no longer thrive.